Assessing public participation in tourism-related urban regeneration: a case of Kochi Heritage City, India / Fazlur Rahman, Norhazliza Halim and Abdul Ahad - Rahman, Fazlur; Halim, Norhazliza; Ahad, Abdul (Universiti Teknologi MARA, Perak, 2022)
In most developing countries, public participation has been considered as a key component for development initiatives. It refers to as an important factor in policymaking for the design and implementation of the urban regeneration process. Despite the continuous demand for participation in regeneration, there is evidence of low participation that has been identified in the assessment of participatory interest. The challenges in participatory approaches providing a sturdy evaluation related to the rapid urbanization of Kochi, India, limits the share of participatory theories for policymakers in the understanding of participation decline. Moreover, it shows difficulties in providing a common state of participation in policy development for tourismrelated urban regeneration. Therefore, the article contributes to a critical examination of public participation in regeneration, which will help in conceptualizing public participation in tourism-related urban regeneration in Kochi. The participatory concept is discussed on the convergence of data collected from literature reviews for the constitution of public participation. The discussion is trying to advocate the opportunities and challenges of the current participation with academic and policy sides, which helps to stimulate future research on participation assessment.